A simple method to estimate renal volume from computed tomography - Breau, Rodney H.; Clark, Edward; Bruner, Bryan; Cervini, Patrick; Atwell, Thomas; Knoll, Greg; Leibovich, Bradley C. (Canadian Urological Association Journal, 2013)
Introduction: Renal parenchymal volume can be used clinically to estimate differential renal function. Unfortunately, conventional methods to determine renal volume from computed tomography (CT) are time-consuming or difficult due to software limitations. We evaluated the accuracy of simple renal measurements to estimate renal volume as compared with estimates made using specialized CT volumetric software. Methods: We reviewed 28 patients with contrast-enhanced abdominal CT. Using a standardized technique, one urologist and one urology resident independently measured renal length, lateral diameter and anterior-posterior diameter. Using the ellipsoid method, the products of the linear measurements were compared to 3D volume measurements made by a radiologist using specialized volumetric software. Results: Linear kidney measurements were highly consistent between the urologist and the urology resident (intraclass correlation coefficients: 0.97 for length, 0.96 for lateral diameter, and 0.90 for anterior-posterior diameter). Average renal volume was 170 (SD: 36) cm3 using the ellipsoid method compared with 186 (SD37) cm3 using volumetric software, for a mean absolute bias of -15.2 (SD 15.0) cm3 and a relative volume bias of -8.2% (p < 0.001). Thirty-one of 56 (55.3%) estimated volumes were within 10% of the 3D measured volume and 54 of 56 (96.4%) were within 30%. Conclusion: Renal volume can be easily approximated from contrast-enhanced CT scans using the ellipsoid method. These findings may obviate the need for 3D volumetric software analysis in certain cases. Prospective validation is warranted.